Harman’s Object-Oriented Ontology: Implications for Environmental Protection among Abraka People of Nigeria - Onotu, Emperor Oborakore; Ikeke, Mark Omorovie (dialektika kontemporer, 2025)
Africans had a rich philosophy in regards to caring for the environment until Western colonization influence crept in and through oil mining spillage which resulted in anti-environmentalism. This also gave ground to the exemption of local farmers and community people from government policymaking. This study used critical analysis of Harman’s Object-Oriented Ontology viewpoint and interviews. The scope of this research is centred on the theory of Graham Harman’s Object-Oriented Ontology (OOO) which breached the separation between human and nonhuman objects and its implications for environmental protection among Abraka people. OOO argues that all environmental objects have inherent value and independence of human beings. This work created a pragmatic connection with Harman’s theory on the Abraka environment and the revitalization of the unadulterated hibernated former culture of the Abraka people on the care of the environment. This research argued that Abraka people should imbibe a culture of self–realization and self–support for the betterment and development of the environment. It concluded that the environment is connected and environmental objects help to shape and reshape each other. And our care of the environment is the bedrock for the survival of humankind.